Spontaneous closure of a post-traumatic macular hole – case report and literature review - Roskal-Wałek, Joanna; Biskup, Michał; Gierada, Magdalena; Odrobina, Dominik (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Ocular trauma may be associated with the formation of full-thickness macular hole. Optical coherence tomography and clinical follow-up enable monitoring of post-traumatic abnormalities. Here we report spontaneous closure of a post-traumatic macular hole in a 14 year-old boy seen in spectral-domain optical coherence tomography.